(NdWADCATX ^ETYRE PREL@DII I FUGI(B. (NDLQ FORTEPIANO(B. (N~ASTX PERWAQ (B( I- XII )s (NfORTEPIONO(B. (NsO^ (B87s - (NdMITRIJ {OSTAKOWI^s ((NmOSKWAs (NsOWETSKIJ KOMPOZTITOR(B.s, 1989)
(NdWADCATX ^ETYRE PREL@DII FUGA DLQ FORTEPIANO(B. (N~ASTX PERWAQ (B.s
Keywords: (NFORTEPIANOs